Det akademiska könet: Kvinnliga forskares erfarenheter av universitetsmiljön - Meurling, Birgitta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2003)
In this article the male dominance of the university is discussed. Studies of academic life indicate that many women feel unfamiliar with the structures within the academy and therefore leave the university to a greater extent than their male colleagues do. I present some mentor projects within my own faculty, that I have coordinated together with a colleague, and discuss with reference to the gender equality plans of the university what possibilities there are for keeping women within academia. There are no simple solutions to this problem, but the first step must be an open discussion within the academy.